Regeneration ability of wheat (Triticum aestivum L.) embryos after bombardment with a particle gun - Némethné Kisgyörgy, Boglárka (Acta Biologica Szegediensis, 2008)
The plant regeneration ability of the spring wheat variety Cadenza from the UK and the winter variety Mv Emese from Hungary was studied over the course of two years. The calli were regenerated with 10 hours illumination in the first year and 14 hours illumination in the second, and the external environment was not completely excluded, light being admitted through a window. The level of plant regeneration was evaluated 7–8 weeks after the isolation of the scutella. Both genotypes exhibited considerable fluctuation in plant regeneration over the two years, but no significant difference was observed in the mean plant regeneration ability of Mv Emese and Cadenza as a function of the two illumination periods.